Analisis Jumlah Nasabah dan Pinjaman yang Disalurkan terhadap Pendapatan Usaha (Studi Kasus: PT. Pegadaian Indonesia) - Andy Fauzi; Bakhtiar Efendi (Ekopem: Jurnal Ekonomi Pembangunan, 2022)
PT. Pegadaian is the only non-bank financial institution in Indonesia that is legally allowed to do financing in credit distribution based on legal liens. The purpose of this research is to analyze the influence of the number of customers and loans distributed to the business income of PT. Pegadaian. This quantitative study uses time-series data from 2011 to 2020 with multiple linear regression methods. From the results of research simultaneously (Simlutan), the number of customers and loans distributed affects the business income of PT. Pedagaian. Partially the number of customers affects the business income of PT. Pawnshops and loans that are distributed affect the business income of PT. Pawnshop. Expected to PT. Pawnshops can increase the number of customers by promoting products and services in PT. Pawnshop.